2021
DOI: 10.1042/bsr20200767
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA NEAT1 promotes glioma cancer progression via regulation of miR-98-5p/BZW1

Abstract: Background: Glioma is the most common malignant tumor in the human central nervous system. Long noncoding RNA nuclear paraspeckle assembly transcript 1 (NEAT1) promotes oncogenesis in various tumors. In the present study, we aimed to examine the role of NEAT1 in altering the properties of gliomas. Methods: Quantitative real-time PCR technology was used to determine the expression levels of relevant genes in tumor tissues and cell lines. The protein expression levels were validated by Western blotting. CCK-8 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…Accumulating reports indicate that lncRNA NEAT1 works as a sponge for miR-98, downregulating its levels in lung cancer and colon cancer cells ( 15 , 24 26 ). Therefore, we postulated that NEAT1 would sponge miR-98 in EC cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulating reports indicate that lncRNA NEAT1 works as a sponge for miR-98, downregulating its levels in lung cancer and colon cancer cells ( 15 , 24 26 ). Therefore, we postulated that NEAT1 would sponge miR-98 in EC cells.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, MRP-7 could be a useful diagnostic and prognostic biomarker, as well as a therapeutic target for EC. The tumor suppressor capability of miR-98 has been demonstrated in numerous human malignancies (15,16), where it negatively regulates cancer cell growth, migration, and invasion. The downregulation of miR-98 has been linked to cisplatin resistance in lung cancer (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies reported increased expression and an oncogenic effect for NEAT1 in glioma (147)(148)(149)(150)(151)(152)(153)(154)(155)(156)(157)(158)(159)(160). NEAT1 increased the activity of several signaling pathways with key roles in the cell cycle, including WNT/b-Catenin and mTOR signaling, leading to increased proliferation, invasion, and metastasis and decreased apoptosis.…”
Section: Role In Tumor Pathologymentioning
confidence: 99%
“…In-vivo therapeutic applications : For many oncogenic lncRNAs, including XIST ( 164 , 169 , 171 ), NEAT1 ( 150 , 158 ), CRNDE ( 173 , 175 , 176 ), TUG1 ( 182 , 183 ), FOXD2-AS1 ( 190 ), HOXA11-AS ( 199 , 201 ), and TP73-AS1 ( 204 , 208 ), and tumor suppressor lncRNAs, including GAS5 ( 214 , 215 ), CASC2 ( 221 ), MATN1-AS1 ( 226 ), animal studies, which are more advanced stages of investigating roles of lncRNAs ( 255 ), validated their effect on glioma. Furthermore, lncRNAs can mediate the effects of anti-cancer drugs.…”
Section: Lncrnas In Gliomamentioning
confidence: 99%